[tex]\sqrt{(\sqrt{3} + \sqrt{5} )^{2} + (\sqrt{3} - \sqrt{5} )^{2} }[/tex]
przyda się wzór: [tex](a + b)^{2} = a^{2} + 2ab + b^{2}[/tex]
oraz podobny: [tex](a - b)^{2} = a^{2} - 2ab + b^{2}[/tex]
[tex]\sqrt{(\sqrt{3} + \sqrt{5} )^{2} + (\sqrt{3} - \sqrt{5} )^{2} } = \sqrt{3 + 2\sqrt{15} + 5 + 3 - 2\sqrt{15} + 5 }[/tex]
po uproszczeniu (skracamy [tex]+2\sqrt{15}[/tex] z [tex]-2\sqrt{15}[/tex])
[tex]\sqrt{3 + 2\sqrt{15} + 5 + 3 - 2\sqrt{15} + 5 } = \sqrt{3 + 5 + 3 + 5} = \sqrt{16} = 4[/tex]
4 jest liczbą wymierną